Management of Youth Creative Sound Broadcasting Program (Pro 2) at Rri Medan in Maintaining Its Existence (Pena Cendekia Insani, 2023)
Managing broadcast programs on radio is not an easy thing, but it is a challenge that must be faced by radio companies. Moreover, managing a radio program means also managing its human resources. However, the success of the program also depends on the quality of the people working in that field. Therefore, good management is needed to realize a successful program. This study examines how the management and obstacles in the management are carried out by Radio Republik Indonesia (RRI) Medan City through planning, organizing, implementing and supervising which are applied to the Suara Creativity Broadcasting Program (Pro 2). This study aims to determine the management and obstacles in the creative sound broadcast program (Pro 2) at RRI Medan in maintaining its existence. This research uses a qualitative approach with descriptive research methods and data collection techniques using observation, interviews, and documentation. This study uses the theory of communication management put forward by George R. Terry. The results of this study indicate that planning as the first step of the program has been going well where the determination of a program idea, broadcast scheduling, and determining broadcast topics have been well formulated. The stage of organizing management is by preparing information to be conveyed through the program that has been prepared. The implementation phase is carried out on air and also publishes information through social media. The monitoring phase is carried out by means of evaluation, in the evaluation of things that are likely to occur can be changed or prevented. As well as obstacles in the implementation of broadcasting are the lack of innovation, the pressure of deadlines and weather conditions.